2011
DOI: 10.1111/j.1463-1326.2011.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of acute pancreatitis in relation to exenatide use

Abstract: Exenatide use was not associated with an increased risk of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 28 publications
3
93
1
2
Order By: Relevance
“…These concerns have been corroborated by reports from adverse event databases (4,5), although such analyses have well-known limitations. In contrast, the observational studies conducted to date have been conflicting and inconclusive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 89%
“…These concerns have been corroborated by reports from adverse event databases (4,5), although such analyses have well-known limitations. In contrast, the observational studies conducted to date have been conflicting and inconclusive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 89%
“…Previously published retrospective studies suggested that the relationship between incretin-based therapy and pancreatitis was nonrandomized and therefore uncontrolled for baseline known and unknown risk factors for pancreatitis. Pancreatitis cases were not blindly adjudicated, which may have led to a bias of overreporting among the incretin-treated patients (4,5,27). The current study is the first in our knowledge to prospectively adjudicate pancreatitis, and therefore, it provides a more precise estimate of the actual rate.…”
Section: Discussionmentioning
confidence: 99%
“…Un risque accru de pancréatite a été évoqué, 31 mais ce point reste controversé. 32 C'est également le cas pour le cancer du pancréas pour les incrétinomimétiques, en général, et pour le cancer médullaire de la thyroïde pour le liraglutide, en particulier. 31 Quoi qu'il en soit, la sécurité à très long terme de ces médicaments doit encore être démontrée 33,34 et seul l'avenir nous dira la place réelle qu'ils vont se ménager dans l'arsenal thérapeutique, de plus en plus complexe, du DT2.…”
Section: Agonistes Des Recepteurs Du Glp-1unclassified